The ecology of the desert-dwelling elephants Loxodonta africana (Blumenbach, 1797) of the western Damaraland and Kaokoland - Bothma, Jacobus du P. (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 1988.